MENGUNGKAP PERISTIWA KEMATIAN KRIMINAL KASUS PEMBEKAPAN PERSPEKTIF MEDIKOLEGAL - Muthaher, Annisa Anwar (Jurnal Forensik dan Medikolegal Indonesia, 2024)
Death is a definite thing in life that can be identified clinically in a person through observing the changes that occur in the corpse's body. The mechanism of death can be unnatural. In this case, wounds were found in the mouth, a form of mechanical smothering. Smothering can cause death, so it is an important reason to discuss and aims to reveal unnatural injuries and what events occurred. The examination method uses the principles of evidence based medicine. On external examination, bruises were found on the inner lips, both eyes (racoon eyes), left cheek, upper jaw, lower jaw, abrasions on the lips with teeth prints, and cheeks and several other bodies injuries. The lips, the tips of both fingers and the tips of the toes were bluish in color and bleeding spots were found on both inner eyelids. The conclusion of the external examination of the corpse showed that the wounds were unnatural and there were signs of strong pressure on the mouth and nose area which could cause suffocation and there were signs of cranial base trauma. These wounds were caused by blunt trauma Key words: Asphyxia, Cranial Base Fracture, smothering